Documenting Art, Writing Biography: Construction of the Silvestre Family History, 1660–1868. (July 2015) - Goodman, Dena; Talbot, Emily
This article concerns six generations of the Silvestre family: a succession of artists, royal drawing masters, and art collectors whose social ascent began in the late seventeenth century in parallel with the Bourbon Monarchy and continued after its fall. In this article, we show how the Silvestres legitimized a path of social mobility from seventeenth-century artisans to nineteenth-century aristocrats by narrating and documenting the family's history in three texts—two catalogues raisonnés that recorded the Silvestre art collections and a family biography that traced the dynasty through the French Revolution. By establishing and advancing the family's reputation or crédit, the Silvestres built a narrative bridge that carried them across the revolutionary divide.